Metabolome and Microbiota Analysis Reveals the Conducive Effect of Pediococcus acidilactici BCC-1 and Xylan Oligosaccharides on Broiler Chickens - Wu, Yuqin; Lei, Zhao; Wang, Youli; Yin, Dafei; Aggrey, Samuel E.; Guo, Yuming; Yuan, Jianmin (Frontiers in Microbiology, 2021)
Xylan oligosaccharides (XOS) can promote proliferation of Pediococcus acidilactic BCC-1, which benefits gut health and growth performance of broilers. The study aimed to investigate the effect of Pediococcus acidilactic BCC-1 and XOS on the gut metabolome and microbiota of broilers. The feed conversion ratio of BBC-1 group, XOS group and combined XOS and BBC-1 groups was lower than the control group (P < 0.05). Combined XOS and BBC-1 supplementation elevated butyrate content of the cecum (P < 0.05) and improved ileum morphology by decreasing muscular layer thickness (P < 0.05) and enhancing the ratio of the villus to crypt depth (P < 0.05). The 16S rDNA results indicated that both XOS and BBC-1 induced high abundance of butyric acid bacteria. XOS treatment elevated Clostridium XIVa and the BBC-1 group enriched Anaerotruncus and Faecalibacterium. In contrast, combined XOS and BBC-1 group induced higher relative abundance of Clostridiaceae XIVa, Clostridiaceae XIVb and Lachnospiraceae. The metabolites in combined XOS and BBC-1 group were enriched in propanoate metabolism as well. Metabolome analysis showed that the XOS and BBC-1 groups enhanced the content of tyrosine precursor 4-hydroxyphenylpyruvate 1 and myo-inositol, respectively (P < 0.05). Notably, combined XOS and BBC-1 supplementation enhanced both allo-inositol and 4-hydroxyphenylpyruvate 1 (P < 0.05). Thus, XOS and BBC-1 may improve the performance of broilers by modulating gut microbiota and metabolome.